2011
DOI: 10.1038/ngeo1218
|View full text |Cite
|
Sign up to set email alerts
|

Ice speed of a calving glacier modulated by small fluctuations in basal water pressure

Abstract: Ice flow acceleration has played a crucial role in the recent rapid retreat of calving glaciers in Alaska 1,2 , as well as in Greenland and Antarctica 3,4 . Fast flow of such glaciers is due primarily to basal ice motion 5 , but its mechanism is poorly understood because subglacial observations are scarce in calving glaciers. Here we show high-frequency ice speed and basal water pressure measurements performed in Glaciar Perito Moreno, a fast-flowing calving glacier in Patagonia. The water pressure was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 29 publications
9
79
0
4
Order By: Relevance
“…The results presented here indicate that changes in basal water pressure leading to velocity changes of this magnitude can in fact have a strong influence on modelled calving rates. The finding supports previous tidewater glacier modelling work (Vieli et al, 2000) and observations at other tidewater glaciers (Kamb et al, 1994;Sugiyama et al, 2011;Danielson and Sharp, 2013) which had already observed a significant dynamic response to changes in basal water pressure, and highlights that changes in basal conditions should not be excluded as an important influence on tidewater glaciers. The link between changes in air temperature and run-off, and changes in velocity may, however, be complicated.…”
Section: Discussionsupporting
confidence: 80%
“…The results presented here indicate that changes in basal water pressure leading to velocity changes of this magnitude can in fact have a strong influence on modelled calving rates. The finding supports previous tidewater glacier modelling work (Vieli et al, 2000) and observations at other tidewater glaciers (Kamb et al, 1994;Sugiyama et al, 2011;Danielson and Sharp, 2013) which had already observed a significant dynamic response to changes in basal water pressure, and highlights that changes in basal conditions should not be excluded as an important influence on tidewater glaciers. The link between changes in air temperature and run-off, and changes in velocity may, however, be complicated.…”
Section: Discussionsupporting
confidence: 80%
“…In order for a dramatic change in the ice dynamics of grounded land-terminating catchments, the ice sheet will need to accelerate substantially in response to rising meltwater inputs. For that to occur requires the maintenance of hydraulically inefficient subglacial drainage and thus a positive relationship between meltwater input and ice motion [61,66]. In contrast, the weight of evidence suggests a seasonal increase in drainage efficiency beneath the GrIS [62,64] with no net acceleration on annual timescales [84,87].…”
Section: Discussion Regarding Future Prioritiesmentioning
confidence: 95%
“…For a number of stable tidewater glaciers in west Greenland, Howat et al [111] reached similar conclusions based on remote sensing of ice velocity 4-6 km from their termini. In stark contrast, Sugiyama et al [66] found a strong correlation between air temperature and ice velocity over two summers at lake-terminating Perito Moreno in Patagonia, indicative of a static hydrological system showing little seasonal evolution, and in which increases in surface melting consistently result in ice acceleration. At the ice sheet scale, Moon et al [112] found evidence for both behaviours.…”
Section: The Influence Of Hydrology On Marine Terminating ('Tidewatermentioning
confidence: 93%
See 1 more Smart Citation
“…Recent observations and modeling studies on either mountain valley glaciers or ice sheets have highlighted the role of subglacial water in ice flow processes (e.g., [1][2][3][4][5]). Studies on polar glaciers have suggested that enhanced melting has induced ice-sheet flow accelerations [6], whereas some modeling analysis indicated that those accelerations were primarily determined by melting supply variability [7] and the speed-up may be offset by efficient subglacial drainage [8].…”
Section: Introductionmentioning
confidence: 99%